(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes of phacoemulsification surgery for brown cataract and to identify intraoperative difficulties. Methods: A retrospective, interventional study without control group was conducted on 36 patients (36 eyes) undergoing phacoemulsification at the Ophthalmology Department, Transport Hospital from January to December 2024. Outcomes assessed included visual acuity, intraocular pressure, complications, and intraoperative challenges. Results: At 1 month postoperatively, 83.3% achieved visual acuity ≥6/10. Postoperative complications included corneal edema (13.9%), hyphema (5.6%), and uveitis (2.8%). The modified “Quick Chop” technique demonstrated high efficacy, with mean phaco time of 1.25 minutes, ultrasound energy 38.4%, and no posterior capsule rupture. Conclusion: Phacoemulsification is a safe and effective method for managing brown cataracts, particularly with the modified “Quick Chop” technique. However, grade V nuclei remain challenging, requiring surgical expertise and advanced equipment